A SINTAKSIS NAHWU DALAM LINGUISTIK BAHASA ARAB KONTEMPORER - muzakki abdurrahman (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2025)
This study examines syntax (nahwu) from the perspective of theoretical Arabic linguistics by positioning grammar not merely as a set of normative rules, but also as a scientific framework that explains the interrelation between form and meaning. The purpose of this research is to describe the concept of syntax in the classical Arabic tradition and to explore its relevance to modern linguistic theories. The study employs a qualitative method with a descriptive-analytical approach based on library research. Data were collected from national and international scholarly journal articles published between 2020 and 2025. The analysis was carried out through reduction, categorization, and interpretation to identify patterns of integration between classical syntax and modern linguistic approaches. The findings reveal that Arabic syntax is not only normative-prescriptive, but also possesses theoretical dimensions that can be integrated with modern linguistics, such as structuralism, generative grammar, and functionalism. Nahwu is shown to serve as a bridge between morphological and semantic aspects while functioning as an essential foundation in teaching, translation, and modern linguistic technologies, including natural language processing. Moreover, the dynamics of Arabic dialectal variation demonstrate the need for a more adaptive syntactic theory that responds to contemporary linguistic realities. Thus, this study affirms that Arabic syntax is a dynamic, adaptive, and relevant system, serving both to preserve the classical heritage and to address academic as well as practical needs in the modern era. Keywords: Arabic Language, Modern Linguistics, Theoretical Linguistics, Syntax.